Reflexões sobre a surdez e o processo de escolarização do sujeito surdo, no município de Arraias-TO - Lima, Monyque Campos (Universidade Federal do Tocantins, 2019)
The present work aims to make a reflection about the deafness and analyze the schooling process of a deaf student. In this research will be approached questions related to the definition of deaf and deaf, a brief history of the deaf subject and their conquests, also highlighting what is Libras, discussions about bilingual education and a brief overview of the education of the deaf in Arraias-TO. Some of the authors used as reference were: Tacca and Martinez (2011), Gesser (2009), Coelho (2011), Strobel (2016), Reis (1992), Rocha (1997), Silva (2000), Strobel Lodi & Lacerda (2014), among others. It was also used LDB n.9394 / 96, LBI nº 13,146 / 2015, Law n. 10,436 / 2002 and documents made available by FENEIS. In this qualitative approach, a field research was carried out with the elaboration of semistructured interview scripts with a deaf student and a teacher, in which it was approached about the process of schooling and formation of both. At the end of the study, it was understood that both the teacher and the deaf student still need to learn more about Libras and make use of it in everyday life to have effective communication, that there are still failures in education regarding the training of specialized professionals to working with students with disabilities, as deaf students end up not having a quality and inclusive education. It was also stressed the importance of including deaf people in regular schools, pointing out that inclusion is not only carried out by the fact that the school has a support teacher who accompanies this student, since one of the school's reasons for becoming inclusive is when student's need is not a barrier so that he can develop along with his classmates.